156k views
3 votes
11. How can you solve the system? Complete the

sentence
(3x + 3y = 9
-6x – 4y = -14
Multiply 3x + 3y = 9 by ?and add
it to -6x – 4y = -14.
X Х

1 Answer

6 votes

Answer:

Multiply by 2.

Explanation:

Given the following simultaneous equations;

3x + 3y = 9 ......equation 1

-6x – 4y = -14 ......equation 2

To solve the equation by elimination, we would multiply eqn 1 by 2;

6x + 6y = 18

-6x – 4y = -14

Adding them together, we have;

0x + 2y = 4

2y = 4

y = 4/2

y = 2

To find the value of x;

3x + 3y = 9

3x + 3(2) = 9

3x + 6 = 9

3x = 9 - 6

3x = 3

x = 3/3

x = 1

Therefore, to solve the system of equations, you will multiply 3x + 3y = 9 by 2 and add it to -6x – 4y = -14.

User Fret
by
5.1k points